INKONSISTENSI INTERNALISASI NILAI TRI HITA KARANA DALAM PRAKTIK MEMBUANG SAMPAH KE TEBA PADA MASYARAKAT DESA SULANGAI, KABUPATEN BADUNG - Ni Made Anggita Sastri Mahadewi; Lulu Kaisa Nafisah; I Dewa Ayu Agung Deanti Maheswari (Yayasan Literasi Sains Indonesia, 2025)
Tri Hita Karana as a harmonious value of human life with God (Parahyangan), fellow humans (Pawongan), and nature/the environment (Palemahan) is often neglected in practice, such as in Sulangai Village, Badung. Residents who routinely throw household waste into their backyards (teba) contribute to environmental pollution. Based on a social construction perspective, there is an inconsistency in the internalization of Tri Hita Karana values ​​in society, whose daily lives touch and depend on nature/the environment. The results show that Tri Hita Karana has not yet become an implemented social reality, while the habit of throwing rubbish into teba has actually been maintained from generation to generation through a dialectical process of externalization-objectivation-internalization. This disparity indicates that the Tri Hita Karana values ​​are less dominant due to entrenched social practices. Collaborative solutions involving residents, village officials, and traditional-religious leaders are needed to strengthen the internalization of Tri Hita Karana, changing teba from a trash can into an ecological space that is in line with Pateman principles. This research highlights the urgency of revitalizing local wisdom through a collective approach to overcoming environmental problems based on cultural values.